Pengenalan dan Pembelajaran Literasi Berbasis Media Digital Mengenai Beretika Media Sosial di SDN Pasir Luhur - Annisa Fitriani Komalasari; Indah Lestari; Sutrisno, Sutrisno; Tabrani Sjafrizal (Yayasan Literasi Sains Indonesia, 2024)
In all-digital era like this, digital literacy is something that must be done in order to keep abreast of the fast technological movements but also to avoid all things that are not desirable in the vast digital media. This journal article aims to be able to find out and provide an understanding of digital literacy regarding the use of Microsoft Word and how to be ethical on social media aimed at elementary school children who are auspices of SDN Pasirluhur to be able to avoid the threat of crime that is rife in the digital world, For example, the spread of fake news on social media and many others. The implementation method used in this article is the stage of monitoring and situation analysis, survey and location determination, learning and socialization with material presentation, as well as the evaluation stage. In activities regarding digital literacy there are several main discussions such as the meaning of social media, the functions and uses of the positive and negative impacts of social media, as well as how to be ethical and deal with fake news on social media.